PENGARUH DISFEMISME DALAM JUDUL BERITA LEMBAGA PERS MAHASISWA RETORIKA - DITA NURMAULIDIA Rizal; NUR FARICHAH AKMALIYAH; SARIFATUL JANNAH; ARJUN SUPRIYANTO; ABDUL WAHAB (Kampus Akademik Publiser, 2026)
Journalistic language plays a crucial role in attracting readers' attention, particularly through the utilization of language style variations such as dysphemism in news headlines. This study aims to identify the distribution of language style variations (dysphemism, euphemism, and orthophemism) in the news headlines of the Student Press Institution (LPM) Retorika at Universitas PGRI Sumenep, as well as to measure their implications for readers' attention (views). The research method employed is descriptive quantitative. The population in this study consisted of 388 news headlines published from September 2025 to May 2026, with a valid sample of 109 news headlines filtered using the Immediate Constituent Analysis (BUL) technique. Data were analyzed using a simple descriptive statistical percentage formula divided into three quarterly periods. The results indicated that accumulatively, the orthophemism style was the most dominantly used (37.6%), followed by euphemism (35.8%) and dysphemism (26.6%). However, the periodic analysis revealed an anomaly in the third quarter (March–May 2026); when the publication quantity and viewership of euphemism and orthophemism plummeted sharply, news headlines categorized as dysphemism instead demonstrated quantitative stability (9 articles) and successfully dominated readers' attention absolutely with a total of 2,127 views. These findings empirically prove that the use of dysphemism in news headlines exerts a strong psychological stimulation effect (clickbait effect) to maintain readership amidst the sluggish circulation of campus information.